The dentist's handbook: Exploring the emerging domain of dental negligence - Ajay R Bhoosreddy; Seema Bhoosreddy; Sonali Vijay Deshmukh; Jaiyesh Bhoosreddy; Priyanka Giri; Aryaman Bhoosreddy (Wolters Kluwer Medknow Publications, 2022)
Medicine is of all the arts the most noble; but, owing to the ignorance of those who practise it, and of those who, inconsiderately, form a judgment of them, it is at present far behind all the other arts. -Hippocrates Every aspect of human activity is influenced by law and dentistry in this regard is no exception. A dentist while providing oral healthcare to patients has to follow certain standards to avoid any litigation in the name of malpractice. Inadequate knowledge regarding the medicolegal aspects halts the effective delivery of oral health-care services. A dentist is bound by law and ethics while providing treatment to patients. Negligence is a breach of legal duty and care that a dental professional has toward his patients. It is necessary that a patient should be aware of complete information regarding the treatment to avoid any clauses of negligence against the doctor even if there is no contract between them. The two main categories under which health-care malpractice can be challenged in court of law is civil and criminal. The third category lies under the Consumer Protection Act 2019 came into force in 2020 in which patient can file lawsuits against the professional services provided by dentists in consumer courts. Studies conducted to assess the level of awareness among the dental and medical professionals have found that they are ignorant about the laws governing their profession. It is essential for health-care professionals to be aware of such laws which would be beneficial not only to the dental professionals and patients but to the society as a whole. Thus, this review provides an overview of negligence, the determination of negligence and its prevention, liabilities of dental professionals which comprehensively form an integral part of the medicolegal aspect of dental practice.